Kajian Teknis Sistem Penyaliran Tambang pada Tambang Terbuka Batubara PT. Nusa Alam Lestari, Kenagarian Sinamar, Kecamatan Asam Jujuhan, Kabupaten Dharmasraya - Arief Rahmat Khusairi; Tamrin Kasim (Journals Mining Engineering : Bina Tambang, 2018)
PT. Nusa Alam Lestari is one of the companies that enganged in coal mining. PT. Nusa Alam Lestari have Izin Usaha Pertambangan (IUP) in Kanagarian Sinamar, Kec. Asam Jujuhan, Kab. Dharmasraya.PT. Nusa Alam Lestari use surface mining system with open pit mine method so it will be forming a basin in mine area. Flows system in PT. Nusa Alam Lestari are using mine dewatering system. Mine dewatering is a flow method to manage the water in mine location for a patch in the sump and drop from mine area with pump. The mine drainase system use to prevent and handle much water come in the mine area with making a channel arround the mine area.The width of the catchment area in east pit PT. Nusa Alam Lestari is 35,16 ha. The maximum capacity of sump to accomodating the runoff debi and underwater debit is 106,462 m3. The form of channels drainage is trapesium in pit mine to reducing the runoff debit  that come in. The pump system that use HDPE pipe type as much as 4 unit centrifugal Sykes HH220i with total maximum head is 92 meter and maximum debit is 230 liter/second.  The result of the pump flows to the settling pond (KPL) with maximum volume is 6.739 m3. The fungtion of settling pond (KPL) is to neutralize harmful substances from pumping result before flows to the river. Keywords: Technical Review, Rainfall, Catchment Area, Sump and Pump.